2012
DOI: 10.1103/physrevb.86.014430
|View full text |Cite
|
Sign up to set email alerts
|

Strain-driven spin-state transition and superexchange interaction in LaCoO3:Abinitiostudy

Abstract: Using spin density functional theory with the Hubbard correction we investigate the magnetic structure of strained LaCoO 3 . We show that beyond biaxial tensile strain of 2.5%, local magnetic moments originating from the high spin (HS) state of Co 3+ emerge in a low spin (LS) Co 3+ matrix. In contrast, we find that compressive strain is not able to stabilize a magnetic state due to geometric constraints. LaCoO 3 accommodates tensile strain via spin state disproportionation resulting in an unusual sublattice st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 58 publications
4
74
0
1
Order By: Relevance
“…Seo et al found in their theoretical calculations that tensile stress can induce ferromagnetically interacting spins on some Co ions at the film/substrate interface. [15] The importance of tensile stress in inducing long-range ferromagnetic order is most convincingly demonstrated by the spintronic device discussed in Hu et al [20] By growing a thin film of LCO on a substrate of SrTiO 3 , the piezoelectric property of the substrate can be used to apply tensile stress to the LCO film to induce ferromagnetism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seo et al found in their theoretical calculations that tensile stress can induce ferromagnetically interacting spins on some Co ions at the film/substrate interface. [15] The importance of tensile stress in inducing long-range ferromagnetic order is most convincingly demonstrated by the spintronic device discussed in Hu et al [20] By growing a thin film of LCO on a substrate of SrTiO 3 , the piezoelectric property of the substrate can be used to apply tensile stress to the LCO film to induce ferromagnetism.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using dynamical mean-field theory in a local density approximation, Krapek et al found that a magnetic state is favored by lattice expansion and that the latter acts as positive feedback for the appearance of local moments [14]. Seo et al argued that strained LCO heterostructures can induce thermal spin state transitions [15]. By depositing LCO thin films onto different substrates, Fuchs et al successfully tuned the ferromagnetic ordering of LCO; [16] an increase in epitaxial strain between the substrate and film was observed to correlate with an increase in the effective magnetic moment µ B /Co.…”
Section: Introductionmentioning
confidence: 99%
“…) electrons in SrTi 1-x Co x O 3-δ and the U eff value can significantly affect both the spin-state and the energy of the occupied 3d levels [36]. Therefore, the choice of U eff has to be consistent with the observed spin state and the valence band density of states.…”
Section: Methodsmentioning
confidence: 99%
“…LaCoO 3 provides a good example as it adopts a low-spin "non-magnetic" ground state in bulk, but exhibits strain-stabilized ferromagnetism in films. [1][2][3] In the doped case, e.g., in bulk La 1-x Sr x CoO 3-δ (LSCO), substitution of Sr 2+ for La 3+ changes the Co valence, inducing metallic ferromagnetism, 4 but also O vacancies. Without the use of high pressures, these vacancies form in high concentrations for x > 0.5-0.6, 5 eventually forming ordered superstructures, as exemplified by Brownmillerite SrCoO 2.5 (SCO).…”
mentioning
confidence: 99%
“…For STO(001)/LSCO and LAO(001)/LSCO, the (013) reflection was chosen. For STO(110)/LSCO, the fourfold in-plane symmetry is broken, and we chose the (310) and (222) reflections to probe two orthogonal high symmetry in-plane directions ( [1][2][3][4][5][6][7][8][9][10] and [001]). In all cases, white crosses mark the positions of the fully strained (pseudomorphic) and fully relaxed (bulk) LSCO reflections.…”
mentioning
confidence: 99%